Determinan Perilaku Seks Pranikah Pada Remaja (15-24 Tahun) Di Indonesia (Analisis SDKI 2017) - Dewi Syafitriani; Indang Trihandini; Julhan Irfandi (Jurnal Kesehatan Komunitas, 2022)
Premarital sexual behavior is one of the adolescent’s problems who are approaching adulthood. Social and cultural transitions that make young people vulnerable to negative impacts. The purpose of the study was to analyze the factors related to premarital sexual behavior in adolescents (15-24 years) in Indonesia in 2017. This study used some of the 2017 IDHS data with a Cross-Sectional design. The number of samples is 23,770 teenagers. Analysis of complex samples using Chi-Square and multivariate analysis using multiple logistic regression predictive models. The result shows premarital sex behavior in adolescents is 7.7%. Factors related to premarital sexual behavior in adolescents are age (POR=4.31;95% CI=3.71-5.02), education (POR=1.82;95% CI=1.55-2.14 ), employment status (POR=2.73; 95% CI: 2.36-3.18), knowledge of reproductive health (POR=1.73; 95% CI: 1.18-2.69), knowledge of contraceptives (POR=1.18;95% CI: 1.52-2.14), attitude (POR=32.05;95% CI: 27.06-37.98), dating style (POR= 68.58 ; 95% CI: 43.93-107.07), and peer influence (POR=18.25 ; 95% CI: 15.44-21.56). The dominant factor for adolescent premarital sex behavior is dating style (POR = 20.09; 95% CI 11.94-33.79:) meaning that adolescents with dating style are at risk of 20 times the risk for premarital sexual behavior. For this reason, it is necessary to increase education for adolescents about the impact of risky dating styles and wrong associations.